2020
DOI: 10.3390/cancers12030606
|View full text |Cite
|
Sign up to set email alerts
|

Combined wIRA-Hyperthermia and Hypofractionated Re-Irradiation in the Treatment of Locally Recurrent Breast Cancer: Evaluation of Therapeutic Outcome Based on a Novel Size Classification

Abstract: Effective tumor control in patients suffering from unresectable locally recurrent breast cancer (LRBC) in pre-irradiated areas can be achieved by re-irradiation combined with superficial hyperthermia. Using this combined modality, total re-irradiation dose and toxicity can be significantly reduced compared to conventionally fractionated treatment schedules with total doses of 60–66 Gy. Applying contact-free, thermography-controlled water-filtered infrared-A superficial hyperthermia, immediately followed by hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Previous studies have reported a variety of techniques for reirradiation to the breast or chest wall including limited radiation fields, electrons, twice-daily radiation, superficial chest wall brachytherapy, concurrent systemic therapy, and hyperthermia. 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Whether improvements in radiation treatment delivery, such as optimized 3-dimensional conformal RT, intensity modulated RT, deep inspiratory breath hold, and particle therapy, increase the therapeutic ratio of reirradiation is not well established. Herein, we report toxicities and outcomes for a cohort of patients with breast cancer treated at a single institution with a second course of repeat breast/chest wall/nodal RT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a variety of techniques for reirradiation to the breast or chest wall including limited radiation fields, electrons, twice-daily radiation, superficial chest wall brachytherapy, concurrent systemic therapy, and hyperthermia. 7 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 Whether improvements in radiation treatment delivery, such as optimized 3-dimensional conformal RT, intensity modulated RT, deep inspiratory breath hold, and particle therapy, increase the therapeutic ratio of reirradiation is not well established. Herein, we report toxicities and outcomes for a cohort of patients with breast cancer treated at a single institution with a second course of repeat breast/chest wall/nodal RT.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pigs are unable to dissipate heat by sweating. Therefore, more human data assessed in superficial tissues under in vivo conditions are needed to verify transferability of results determined in this study for piglets although comparable data in humans have already been reported [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For clinical application, additional consideration of significant influencing factors is recommended in order to enable adequate tissue heating of patients, e.g.…”
Section: Quantitymentioning
confidence: 85%
“…Upon wIRA-heating of superficial recurrences of breast cancers, Notter et al [14] reported mean tissue temperatures between 42 C at the skin surface and about 40 C at a depth of 20 mm after reaching thermal steady state. These data agree with heating states assessed in piglets and which are comparable with tissue temperatures previously reported for various therapeutic applications of wIRA [2][3][4][5][6][7][8][9][10][11][12][13]15].…”
Section: Percentiles Of Temperature Data and Values Of T 90 T 50 mentioning
confidence: 99%
See 1 more Smart Citation
“…wIRAR has both, temperature-dependent and non-dependent effects, which are without relevant thermal energy transfer and/or relevant temperature changes [16]. It is therefore not only used in acute and chronic wound healing as it promotes perfusion, alleviates pain and has antiinfectious effects [17], but is also used in oncology [18], dermatology [16] and rheumatology [12]. Until now, wIRAR has only been use in rheumatology and especially in treating axSpA as a whole-body treatment.…”
Section: Introductionmentioning
confidence: 99%